2016
DOI: 10.1021/acs.chemrestox.6b00188
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Aerosol from an E-Cigarette: A Quantitative Comparison with Cigarette Smoke

Abstract: There is interest in the relative toxicities of emissions from electronic cigarettes and tobacco cigarettes. Lists of cigarette smoke priority toxicants have been developed to focus regulatory initiatives. However, a comprehensive assessment of e-cigarette chemical emissions including all tobacco smoke Harmful and Potentially Harmful Constituents, and additional toxic species reportedly present in e-cigarette emissions, is lacking. We examined 150 chemical emissions from an e-cigarette (Vype ePen), a reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
346
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(393 citation statements)
references
References 55 publications
29
346
4
1
Order By: Relevance
“…Furthermore, Margham et al reported a nicotine dose per puff of 0.032 mg of nicotine for the Vype ePen and 0.17 mg for 3R4F smoked at a variant of the HCI regimen (CORESTA CRM81), and HCI, respectively. Based on these numbers there is overall a good agreement between the data from Margham and colleagues 30 and the dilution ratio we used for 3R4F and Vype ePen to achieve nicotine dose matching and one e-cigarette dose exceeding 3R4F nicotine by approximately two-fold. After one-hour exposure, different endpoints were investigated at 24 hrs and 48 hrs post treatment, including total RNA for differential RNA-seq profiling.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, Margham et al reported a nicotine dose per puff of 0.032 mg of nicotine for the Vype ePen and 0.17 mg for 3R4F smoked at a variant of the HCI regimen (CORESTA CRM81), and HCI, respectively. Based on these numbers there is overall a good agreement between the data from Margham and colleagues 30 and the dilution ratio we used for 3R4F and Vype ePen to achieve nicotine dose matching and one e-cigarette dose exceeding 3R4F nicotine by approximately two-fold. After one-hour exposure, different endpoints were investigated at 24 hrs and 48 hrs post treatment, including total RNA for differential RNA-seq profiling.…”
Section: Discussionsupporting
confidence: 66%
“…The commercially available Vype ePen e-cigarette (Nicoventures, UK) is a closed modular device and the 'Blended Tobacco' variant was used containing18 mg/ml nicotine replaceable e-liquid cartridge composed of 25% (w/w) propylene glycol, 48.14% vegetable glycerine, 25% water, and (<1%) blended tobacco flavor 30 .…”
Section: Methodsmentioning
confidence: 99%
“…formaldehyde, acetaldehyde, acrolein, and toluene) are significantly lower (9- to 450-fold lower) than those in cigarette smoke [20, 24], and in many cases (e.g., NNN and NNK) comparable with the trace amounts present in nicotine replacement products [25ā€“27]. However, recent studies, have shown that specific toxicants and carcinogens present in EC aerosols can reach levels equal (e.g., acetaldehyde and chromium) to or exceeding (e.g., formaldehyde, and nickel) to those found in cigarette smoke, particularly as the power of the device increases [15, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the negative consequences of eā€cigarettes, including their impact on the cardiovascular system,7 remain a subject of debate, especially in light of the fact they are not emissionā€free devices. To this end, eā€cigarettes in fact share some of the toxicant profile of conventional cigarette smoking and may expose users to similar health risks 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%